Development of the Bruton's tyrosine kinase inhibitor ibrutinib for B cell malignancies. Issue 1 (8th September 2015) - Gayko, Urte; Fung, Mann; Clow, Fong; Sun, Steven; Faust, Elizabeth; Price, Samiyeh; James, Danelle; Doyle, Margaret; Bari, Samina; Zhuang, Sen Hong
Abstract : Ibrutinib is a first‐in‐class oral covalent inhibitor of Bruton's tyrosine kinase that has demonstrated clinical benefit for many patients with B cell malignancies. Positive results in initial trials led the U.S. Food and Drug Administration to grant ibrutinib three breakthrough therapy designations for mantle cell lymphoma (MCL), del17p chronic lymphocytic leukemia (CLL), and Waldenström's macroglobulinemia (WM). Ibrutinib was approved for these three cancers within 14 months of the original U.S. approval. Additionally, ibrutinib is approved for patient subsets with MCL and/or CLL in >45 other countries. Via a unique mechanism of action, ibrutinib inhibits B cell signaling pathways that regulate the survival, proliferation, adhesion, and homing of cancerous cells. This marks a paradigm shift from the conventional cytotoxic chemotherapy approach to treating B cell malignancies. Ibrutinib continues to be evaluated across a range of B cell malignancies, either as single‐agent therapy or in combination with other therapies, and continues to transform the lives of these patients.